TELAAH PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA PENGANIAYAAN BERAT DALAM PUTUSAN NOMOR 209/PID.B/2023/PN.SKT - Fadhillah Nur Fitriyani; Bambang Santoso (Verstek, 2025)
This study analyzes the principles of restorative justice and finds out the judge's considerations in deciding cases of serious assault based on the study of verdict number 209/Pid. B/2023/PN Skt. The purpose of this legal research is to find out the basis for the judge's considerations in deciding cases by applying the principle of restorative justice based on the study of verdict number 209/Pid. B/2023/PN Skt. This legal writing is a normative legal research with a prescriptive and applied nature using primary legal materials and secondary legal materials. The technique of collecting legal materials is using a literature study with a case approach. The analysis technique used is the deductive syllogism method. Based on the results of the study and discussion, the suitability of the Judge's considerations in issuing a light criminal sentence in the crime of serious assault, the author is in accordance with the principles of restorative justice. The judge's decision also reflects a sense of justice and benefit, because all parties involved, both the defendant, the victim, and the community, can feel a sense of peace, which is like the principle of restorative justice, namely prioritizing the recovery of the victim, the defendant, and the community.